2011
DOI: 10.5141/jefb.2011.044
|View full text |Cite
|
Sign up to set email alerts
|

The role of macrophytes in wetland ecosystems

Abstract: Aquatic macrophytes, often also called hydrophytes, are key components of aquatic and wetland ecosystems. This review is to briefly summarizes various macrophyte classifications, and covers numerous aspects of macrophytes' role in wetland ecosystems, namely in nutrient cycling. The most widely accepted macrophyte classification differentiates between freely floating macrophytes and those attached to the substrate, with the attached, or rooted macrophytes further divided into three categories: floating-leaved, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(38 citation statements)
references
References 112 publications
1
33
0
4
Order By: Relevance
“…Wetland rhizospheres have been extensively studied with respect to microorganism communities [29]. It has been shown that the root exudates from different plants could direct the different development of microbial communities [30].…”
Section: Discussionmentioning
confidence: 99%
“…Wetland rhizospheres have been extensively studied with respect to microorganism communities [29]. It has been shown that the root exudates from different plants could direct the different development of microbial communities [30].…”
Section: Discussionmentioning
confidence: 99%
“…P. thunbergii is occasionally problematic in constructed wetlands (Kim et al, 2011;Choe et al, 2010). Wetlands are especially vulnerable to plant invasion due to frequent disturbance and high nutrient levels (Rejmankova, 2011), and P. thunbergii can become the dominant species in constructed wetlands. However, there have been few ecological studies on P. thunbergii, and the lack of data makes it difficult to understand its ecological characteristics and manage its prevalence in wetlands.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from those, other important factors of the plant composition in wetlands include fertility, salinity, competitiveness between plants and herbivores (Keddy 2000). Soil fertility is also a determinant of plant community and diversity in wetlands (Weiher and Keddy 1995) because wetland soils are both the medium in which many of the wetland chemical transformations take place and the primary storage of available chemicals for most wetland plants (Mitsch and Gosselink 2007), so that nutrient enrichment could increase growth of invasive species (Green and Galatowitsch 2002, Kercher and Zedler 2004, Rickey and Anderson 2004, Rejmankova 2011) and these environmental conditions could lead a different stage of succession.…”
Section: Study Sitesmentioning
confidence: 99%